2008
DOI: 10.1007/s11150-008-9041-6
|View full text |Cite
|
Sign up to set email alerts
|

Registered domestic partnerships among gay men and lesbians: the role of economic factors

Abstract: Economics of household, Sexual orientation, Lesbian and gay issues, Marriage, Domestic partnership, Same-sex couples, J12, J16, J18,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
(22 reference statements)
1
14
0
1
Order By: Relevance
“…These findings remind us that by conditioning on partnership/marriage entry in a country where a high proportion of couples chose informal cohabitation, we are dealing with a (positively) selected sample. The extent to which this is more true of the homosexual sample is hard to ascertain because the underlying population is unknown, but this conjecture would be consistent with the literature (Badgett et al 2008).…”
Section: Descriptive Statisticssupporting
confidence: 78%
“…These findings remind us that by conditioning on partnership/marriage entry in a country where a high proportion of couples chose informal cohabitation, we are dealing with a (positively) selected sample. The extent to which this is more true of the homosexual sample is hard to ascertain because the underlying population is unknown, but this conjecture would be consistent with the literature (Badgett et al 2008).…”
Section: Descriptive Statisticssupporting
confidence: 78%
“…This pattern is also established by Klawitter (2008). Lee Badgett et al (2008) analyze data collected among self-identified same-sex couple in California, before the state legalized same-sex marriage, finding that economic motivations to register a partnership were limited. 1…”
Section: Introductionmentioning
confidence: 73%
“…Thus, married and cohabiting same-sex families would be more socioeconomically similar to one another. This similarity may reflect the fact that the modestly privileged benefits and protections that same-sex couples have gained in recent years through the legalization of marriage are artificially diluted—relative to those enjoyed by different-sex couples who marry—by a lack of benefits and protections for same-sex Americans in other areas of social life (Ash and Badgett 2006; Badgett et al 2008; Black et al 2007b; Burgoyne 2012; Gates 2013; Heck et al 2006; Williams 2012). …”
Section: Exploring the Role Of Family Socioeconomic Resourcesmentioning
confidence: 99%